Keefektifan Pendekatan CTL dan Problem Solving Ditinjau dari Prestasi Belajar Matematika dan Religiusitas Siswa - Tri Wijayanti; Sugiman Sugiman (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2013)
Penelitian ini adalah penelitian eksperimen semu dengan desain nonequivalent controlgroup design. Populasi penelitian ini adalah siswa kelas VII di sekolah berbasis pesantren yaitu SMP Muhammadiyah Boarding School (MBS) Yogyakarta. Sampel penelitian adalah kelas VII C, VII D, dan VII E. Instrumen penelitian ini adalah angket religiusitas siswa dan tes prestasi belajar matematika. Data dianalisis secara multivariat dengan taraf signifikansi 5% untuk pengujian kesamaan rata-rata kelompok dan ditindak lanjuti dengan analisis univariat pada taraf signifikansi 5%. Hasil penelitian menunjukkan bahwa (1) pendekatan CTL efektif ditinjau dari prestasi belajar matematika dan religiusitas siswa, (2) pendekatan problem solving efektif ditinjau dari prestasi belajar matematika dan religiusitas siswa, dan (3) pendekatan CTL tidak lebih efektif dibandingkan pendekatan problem solving ditinjau dari prestasi belajar matematika dan religiusitas siswa.Kata kunci: pendekatan contextual teaching and learning (CTL), pendekatan problem solving, prestasi belajar matematika, religiusitas siswa The Effectiveness of CTL and Problem Solving Approach in Terms of Student’s Mathematics Achievement and Religiosity AbstractThis study is aquasi-experimental research design with nonequivalent control group design. The study population was a class VII student of SMP Muhammadiyah Boarding School (MBS) Yogyakarta as islamic boarding school. Samples were class VIIC, VIID, and VIIE. The research instrument was a questionnaire religiosity students and mathematics achievement tests. Data were analyzed by the multivariate analysis at the significance level of 5% for the average similarity testing groups and followed up by a univariate analysis at the significance level of 5%. The results showed that (1) CTL approach effective in terms of student’s mathematics achievement and religiosity, (2) problem solving approach effective in terms of student’s mathematics achievement and religiosity, and (3) CTL approach is not more effective than problem solving approach in terms of student’s mathematics achievement and religiosity.Keywords: contextual teaching andlearning(CTL) approach, problem solving approach, mathematics achievement, studentreligiosity